Vitamin D and Human Health - Simon Spedding (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Over the past decades, researchers have gathered data demonstrating that vitamin D and its metabolites possess activities far beyond the classic regulation of calcium-phosphate homeostasis. It is now well established that vitamin D is essential for the proper functioning of the musculoskeletal, cardiovascular, nervous, and immune systems. Furthermore, vitamin D and its analogs were shown to regulate proliferation and differentiation of keratinocyte, immune cells, and numerous cancer-derived cells, both in vivo and in vitro. On the other hand, population base studies have provided evidence that global vitamin D deficiency is correlated with the occurrence and aggravation of symptoms of skeletal, cardiovascular autoimmune, and skin disease; infections; metabolic and cognitive disorders; multiple types of cancers; as well as overall mortality. This Special Issue of International Journal of Molecular Sciences, entitled "Vitamin D and Human Health", summarizes recent advances in our understanding of pleiotropic activity of vitamin D with a focus on its protective role against cancer, hypertension, viral infections, and neurological diseases, as well as its impact on the immune system and mitochondria. Furthermore, eight research papers provide new insight into vitamin D research and highlight new directions and targets in the prevention and treatment of human diseases.